The Guidelines of Loyalty Building for Employees in Automotive Industry Organization in Rayong Province - รักวงษ์ ปรนรรณ (Journal of Industrial Business Administration, 2019)
The purpose of this research was to study the guidelines of loyalty building for employees in automotive Industry organization in Rayong province. The samples were 130 persons by random sampling methods. A questionnaire was used as the research tool and analysis data by SPSS programming in function of frequency, percentage, mean, standard deviation, Independent Samples t-test and one-way ANOVA. The results were found that most respondents were male, aged between 25 - 30 years old, married, had a bachelor’s degree, officer, most of people from Logistics, an average monthly income of THB 20,000 - 40,000 and 2 – 4 years of work experience. Most recognized the aspects for the guidelines of loyalty building for employees in automotive Industry organization in Rayong as a whole, a high level. The detail in each side. It was found that 2 items of the high level for team work always supporting and second is the attitude are safety of working area must be clear. 1 item of the high level for behavior is the big support from colleagues to data and 1 item of the high level for knowledge is Recognition also have standards as same as benefits for employees all position. The comparison data results of average differential for the guidelines of loyalty building for employees in automotive Industry organization in Rayong province. Based on personal status, age, education monthly income and work experience, with a statistical significance level of .05